Progress in studying the fretting wear/corrosion of nuclear steam generator tubes. (1st September 2020) - Guo, Xianglong; Lai, Ping; Li, Ling; Tang, Lichen; Zhang, Lefu
Highlights: The current understanding of the fretting wear/corrosion response of materials for nuclear SG tube was reviewed. The experimental programs and techniques used previously were described. The effects of environmental and mechanical parameters on fretting wear were analyzed. The microstructure evolution was summarized. Abstract: Revealing the fretting failure law and mechanism of steam generator tubes is a critical issue to ensure the safe operation of nuclear power plants. This paper reviews the current understanding of the response of nuclear steam generator tube materials (Alloy 600, Alloy 690 and Alloy 800) to fretting wear, focusing on the effects of environment factors (temperature, pH and oxygen content), mechanical parameters (sliding amplitude, normal force and frequency) and materials state (grain size, carbide volume fraction, size and distribution, and surface treatment). Related characterization work has also been reviewed to discuss the fretting corrosion and failure mechanism of the materials. The future research direction that should be taken for the improvement of the understanding of the fretting wear of steam generator tubes has been suggested.